Paradoxurile istoricului în Hronicul Vechimei a romano-moldo-vlahilor - Gabriel Mihăilescu (Revista de Istorie și Teorie Literară)
We have resolved to identify the structure of Cantemir’s paradoxes in Hronicul vechimei a romano-moldo-vlahilor. Their opposite terms both result out of his humanistic culture and education. In order to achieve this goal we analysed on the one hand the defining elements of the critical rationalism found in his Hronic through which history is subjected to thorough processes of demythologization, removal of rhetoric, and objectification. On the other hand, we attempted to emphasize an opposite movement against historical criticism, i.e. promoting traditional mythical structures or establishing a new historical mythology of humanistic nature due to which Dimitrie Cantemir is now considered one of the main forerunners of modern nationalism.